2013
DOI: 10.1177/0907568213490205
|View full text |Cite
|
Sign up to set email alerts
|

Voicing the child? A case study in Finnish early childhood education

Abstract: Contemporary Nordic early childhood education and care takes as its starting point the individual and 'competent' child and emphasizes the aim to take account of children's views. It is also common in educational settings that the child's views are documented and thus transformed into contexts in which they are discussed between the adults. In light of a case study of 22 parent-teacher meetings in Finnish early childhood education and care the article discusses the position of the child's voice in this context… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 34 publications
1
31
0
1
Order By: Relevance
“…), at least regarding its implications for negotiating napping practices in ECEC, since no such negotiations were actualised (cf. Alasuutari, ). Instead, the analysis showed how both practitioners and parents resisted these implications by drawing on a naturalised discourse of napping and on a discourse that defined the child as problematic or as having internal deficiencies, when he or she did not fall asleep as expected.…”
Section: Resultsmentioning
confidence: 99%
“…), at least regarding its implications for negotiating napping practices in ECEC, since no such negotiations were actualised (cf. Alasuutari, ). Instead, the analysis showed how both practitioners and parents resisted these implications by drawing on a naturalised discourse of napping and on a discourse that defined the child as problematic or as having internal deficiencies, when he or she did not fall asleep as expected.…”
Section: Resultsmentioning
confidence: 99%
“…socially accepted showed that certain types of initiatives remain unseen. Although the discourse of a competent child may dominate the educational discourse, it is too simplified to expect that it would be the predominant approach in educational practices (Alasuutari 2014).…”
Section: Discussion and Implications For Research And Practicementioning
confidence: 99%
“…In the Nordic curricula, children are seen as active, competent, developing and learning. (Alasuutari, 2014) This reflect the viewpoint of sociological research of childhood where children are sen active agents of their live (Corsaro, 2011). Furthermore, equality and the ideal of universal access of ECE services is central in the Nordic educational policies (Karila, 2012).…”
Section: Introductionmentioning
confidence: 92%
“…Alasuutari (2014) also found that the parents' role in partnership discussions was restricted to what concerned the individual child: parents did not have a say in the more general educational practices of ECEC. These findings lead us to wonder if this holds even in partnerships for bilingualism; if so, it would mean that parents do not have a say in the choice of e.g.…”
Section: Ecec Partnerships In Finlandmentioning
confidence: 99%